PENGARUH PENGELASAN LISTRIK TERHADAP SIFAT MEKANIK PADA ALAT ANGKAT KENDARAAN NIAGA KAPASITAS 2 TON - Hendra Tumurang; Rudy Poeng; Romels C A Lumintang (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2014)
In the process of the commercial vehicle lifting equipment production, there are many joining processes done by using electric welding. To find out the effect of the process, the tensile strength of the welding process is necessary to be tested. The information of welding strength on the commercial vehicle components is obtainable from the tensile test that has been done over the twelve specimens with the standard rectangular cross-section from the result of welding process. The results of the tensile test show the data of loading and extension that occurred which was then processed to obtain the value of the stress, strain and curves of each specimen. Testing from the specimen it is obtained that the yield strength 461.538 N/mm2, the tensile strength of 536.325 N/mm2, tenacity 2,451%, the elastic modulus of 353.955 N/mm2, resilience and toughness 0.652 and 876.363 N/mm2, with an error rate of 5%. The strength of the electric welding showed no significant difference compared to the strength without joining, and did not provide a great influence on the mechanical properties of commercial vehicle components lifting capacity of 2 tons, with an error of 5%. From this experiment it is concluded that electric welding on the equipment can provide sufficient safety. Keywords: Vehicle lifting components, electric welding, mechanical properties